Observed and projected urban extreme rainfall events in India. Issue 22 (28th November 2014) - Ali, Haider; Mishra, Vimal; Pai, D. S.
Abstract We examine changes in extreme rainfall indices over 57 major urban areas in India under the observed (1901–2010) and projected future climate (2010–2060). Between 1901 and 2010, only four out of the total 57 urban areas showed a significant (p‐value <0.05) increasing trend in the monsoon maximum rainfall (MMR). Time‐varying trends for the various rainfall indices exhibited that only a few urban areas experienced significant increases in the extreme rainfall indices for the different periods. Moreover, rainfall maxima for 1–10 day durations and at 100 year return period did not change significantly over the majority of urban areas in the post‐1955 period. Results do not indicate any significant change (p > 0.05) in the pooled mean and distribution of the extreme rainfall indices for the pre‐ and post‐1983 periods revealing an insignificant role of urbanization on rainfall extremes in the major urban areas in India. We find that at the majority of urban areas changes in the extreme rainfall indices are driven by large scale climate variability. Regional Climate Models (RCMs) that participated in the CORDEX‐South Asia program showed a significant bias in the monsoon maximum rainfall and rainfall maxima at 100 year return period for the majority of urban areas. For instance, most of the models fail to simulate rainfall maxima within ±10% bias, which can be considered appropriate for a storm water design at many urban areas. Rainfall maxima at 1–3 day durations and 100 year return period is projected to increase significantly under the projected future climate at the majority of urban areas in India. The number of urban areas with significant increases in rainfall maxima under the projected future climate is far larger than the number of areas that experienced significant changes in the historic climate (1901–2010), which warrants a careful attention for urban storm water infrastructure planning and management.